HANDLING DYSLEXIA THROUGH READING LEARNING METHODS IN MADRASAH ENVIRONMENTS - Yahya Sudarsono; Kholilur Rahman; Fathi Hidayah (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2024)
This research focuses on treating Dyslexia through reading learning methods in a madrasah environment. This research aims to identify and develop effective learning methods for dyslexic students, as well as evaluate the impact of these approaches in the context of madrasah education. This research uses a qualitative approach with case studies. Data was collected through observation, in-depth interviews with teachers and students, and documentation studies at research locations in Madrasas. The research results show that teachers' understanding of Dyslexia is still limited. However, multisensory approaches and the use of technology in learning have proven effective in improving the reading abilities of dyslexic students. In addition, collaboration between madrasas and parents plays an important role in supporting students' academic progress and self-confidence. Implementing comprehensive and collaborative learning methods can provide significant results in improving the quality of inclusive education in madrasas. The implications of this research emphasize the importance of training for teachers to increase their understanding of Dyslexia, as well as the adoption of multisensory and technological approaches to learning. Parental support and active involvement are also very necessary to ensure continued progress for dyslexic students. The results of this research can provide practical guidance for madrasas in developing more inclusive and effective learning strategies.